An Evaluation of the Effects of the 1755 Lisbon Earthquake on Rivers and Their Tributaries in Mainland Portugal - Alice Tavares; Aníbal Costa; Carlos S. Oliveira (Hydrology, 2025)
Historical earthquake records are crucial for analyzing high-intensity earthquakes that occur over long periods. Since good instrumental data only date back to 1980, there are gaps in our knowledge, and qualitative assessments remain essential to expand our knowledge and integrate more information into the number of variables under analysis. This study examined the hydrological and hydrogeological effects of the 1755 Lisbon earthquake, focusing on regions near rivers and proposing new insights for intensity scales. This information is relevant for seismic risk management and mitigation, to be discussed in regional and national territorial planning strategies. Mapping revealed that most phenomena occurred along the Porto–Tomar tectonic fault, with some extending to other probable faults or geological contrasts. A comparative chart between existing intensity scales and the proposed descriptors highlights agreements and discrepancies, emphasizing the need for more detailed descriptors for intensity levels below X for river-related phenomena. The proposed descriptors include a flow increase with course alterations (intensities VI–VIII), flow suppression and eventual reset (intensity VIII or higher), abnormal current agitation and vertical wave movements (intensities VI–VIII), and cloudy (turbid) water (intensities V–VIII). This work also highlights the need to cross-reference data and the complexity of establishing correlations between effects, ancient descriptions, and descriptors for these intensity scales.